The prevalence and associated clinical correlates of hyperuricemia in patients with bipolar disorder - Li, Shuyun; Lu, Xiaobing; Chen, Xiaodong; Huang, Zebin; Zhou, Hui; Li, Zezhi; Ning, Yuping (Frontiers in Neuroscience, 2022)
Objective: The prevalence and clinically associated factors of hyperuricemia (HUA) have been widely studied in the general population but rarely in patients with bipolar disorder (BPD) co-morbid with HUA. This study attempted to investigate the prevalence of HUA in BPD patients and analyze the associated correlates of HUA. Methods: In this study, 182 outpatients with BPD and 182 healthy controls participated. The demographic and clinical information were collected. The body weight, height, waist circumference (WC), hip circumference (HC), and blood pressure (BP) were measured. The levels of serum uric acid (UA), triglyceride (TG), high-density lipoprotein (HDL-C), and fasting blood glucose (FBG) were also determined. Results: BPD patients had a significantly higher prevalence of HUA (40.7%) compared to healthy controls (30.2%) (χ2=4.335, P=0.037). The systolic blood pressure (SBP), pulse pressure (PP), FBG, UA, and body mass index (BMI) were higher in the BPD group compared with those in the control group, while the diastolic blood pressure (DBP), and HDL-C level were lower (P<0.05) in BPD patients. The prevalence of HUA was higher in BPD patients who used antipsychotics combined with mood stabilizers than that in BPD subjects receiving the mood stabilizers alone (P<0.001). The prevalence of HUA and increased serum UA levels were higher in the manic group (62.1%) than in the depressive (34.3%) or euthymia group (17.0%) (P<0.001). Additionally, the severity of mania was positively correlated with the UA level (r=0.410, P<0.001). There were significant differences in terms of MetS (29.7% vs. 14.8%), BMI, HC, WC, TG, and HDL-C between the HUA and the non-HUA groups (P<0.05). The unconditional logistic regression analysis revealed that high BMI (OR=1.210; 95%CI: 1.100-1.331), and high TG level (OR=1.652; 95%CI: 1.058-2.580) were the major risk factors for HUA in BPD patients. Conclusion: Our study suggests that patients with BPD are prone to metabolic diseases such as HUA. Higher serum levels of TG and high BMI could be associated with HUA development. Clinicians need to regularly monitor and evaluate BPD patients for their serum UA levels, especially for BPD patients with manic/hypomanic episodes and/or under the treatment of antipsychotics combined with mood stabilizers.